Effect of a medicinal plant (Passiflora incarnata L) on sleep - Guerrero, Fructuoso Ayala; Medina, Graciela Mexicano (Sleep Science, 2017)
INTRODUCTION: Extracts of the plant Passiflora incarnata L. (Passifloraceae) were administered intraperitoneally in order to test its effects on sleep. METHOD: Experiments were carried out on chronically implanted male adult wistar rats to obtain cerebral (EEG), ocular (EOG) and muscular (EMG) activities throughout their states of vigilance. Polygraphic recordings were taken during 9 continuous hours before and after the extract administration (500 mg/kg). RESULTS:Passiflora incarnata induced a significant increment in the total sleep time (p<0.05). This increment was due to an increase in the time spent by animals in slow wave sleep (SWS). Concomitantly, a significant decrement in wakefulness (W) was observed (p<0.05). In contrast, time spent in rapid eye movement (REM) sleep showed a decreasing tendency, since both its frequency and mean duration were reduced. CONCLUSIONS: The extracts obtained from Passiflora incarnata can be considered as appropriated sleep inducers.
Keywords: Passifloraceae; Sleep Aids, Pharmaceutical; Insomnia; Sleep; Sleep, REM